SNAPE’S AMBIGUOUS BEHAVIORS IN HARRY POTTER AND THE DEATHLY HALLOWS - ERIK TRICAHYO SYAH (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2014)
Abstrak Snape sebagai salah satu minor karakter di dalam karya fiksi dari penulis J.K Rowling, Harry Potter And The Deathly Hallows, digambarkan sebagai salah satu karakter protagonist dan antagonis dalam satu cerita. Selama dalam perkembangan cerita, Snape mencerminkan sikap loyalitas ke kedua belah, Dumbledore dan Voldemort. Kedua belah pihak tersebut sangat meyakini jika Snape sangat loyal kepada mereka, sehingga memungkinkan Snape sebagai Double Agent. Meskipun Snape berpihak kepada Dombledore dan Voldemort, Snape sebenarnya tidak memilih untuk berpihak kepada pihak tertentu. Snape satu-satunya karakter yang dapat dikatakan sebagai Hero dan Anti-Hero. Sikap inilah dalam kajian behaviorisme disebut ambiguous behavior. Factor-faktor yang mempengaruhi perilaku Snape tersebut tidak terlepas dari pengalaman masa lalu. Dari sudut pandang behaviorisme, kasus Snape tersebut disebabkan oleh factor personal dan factor lingkungan. Dari factor personal, Snape memiliki sikap jahat terutama kepada yang menyakitinya. Ini disebabkan karena masa kecilnya dimana Snape selalu menjadi korban kejahatan dari temannya. Kata Kunci: Anti-Hero, perilaku, sikap, lingkungan, personal, hero, perngalaman masa lalu. Abstract Snape as one minor character in the work Harry Potter And The Deathly Hallows from author J.K Rowling showing up both as good and evil role. Snape's actions throughout the series have shown service to each of the opposing sides. Both Dumbledore and Voldemort believe Snape is only loyal to them, allowing him to work as a double agent. Not only is it unknown until very near the end of the final book which side he is really on, but there is no concrete evidence until then that he has actually chosen one. He has made strong claims, which Dumbledore trusts, to oppose Lord Voldemort's cruelty, but hatred exists between himself and many Order of the Phoenix members. Snape exhibits both good and evil qualities, making him the series' only anti-hero. This kind of behavior is called ambiguous behaviors in behaviorism scope. The factors behind this phenomenon may vary depends on his or her experience. But in Snape case, personal and environmental factors are the reason behind Snape’s ambiguous behaviors. Snape possesses a nasty demeanour, and is especially retaliatory to those who hurt him. However, Snape's seeming cruelty may have resulted from a terrible childhood and early youth. When Harry delved into Snape's early memories, there was nothing good to be seen, only an abusive father, a victimized mother, derisive classmates, and a cruel James Potter and Sirius Black. While the series does little to emphasize Snape's good qualities, it is implied, at least until the end of Harry Potter and the Half-Blood Prince, that he would protect Order of the Phoenix members with his life. He has saved Harry's life on more than one occasion, though it might take a particularly observant reader to see that. Though he treats students badly and is seemingly indifferent to their feelings or situations, he wants them to learn valuable lessons. Keywords:Attitude, anti-hero, behavior, environment, hero, past-experience, and personality